2019
DOI: 10.1017/s0144686x19000837
|View full text |Cite
|
Sign up to set email alerts
|

‘It's most of my life – going to the pub or the group’: the social networks of involuntarily childless older men

Abstract: The social networks of older people are a significant influence on their health and wellbeing. Adult children are an important element in their parent's network and provide the majority of informal care. The morphology of personal networks alters with age, employment, gender and relationships. Not having children automatically reduces both vertical familial structure and affects the wider formal and informal social links that children can bring. Childless men are missing from gerontological, reproduction, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 108 publications
(113 reference statements)
0
9
0
1
Order By: Relevance
“…Recreational and leisure activities offer opportunities that bring people with similar hobbies together and open the doors to socialization and communication. It has been an issue of concern about how people can be kept busy within these constraints, whether social relationships will continue and how they can be maintained if they can continue (Genoe et al, 2018;Hadley, 2019;Parnell, 2020). As a result of this research, it has been determined that the same problems arise in the individuals staying home and recreational activity with family members are an important solution tool for overcoming these problems.…”
Section: Discussionmentioning
confidence: 99%
“…Recreational and leisure activities offer opportunities that bring people with similar hobbies together and open the doors to socialization and communication. It has been an issue of concern about how people can be kept busy within these constraints, whether social relationships will continue and how they can be maintained if they can continue (Genoe et al, 2018;Hadley, 2019;Parnell, 2020). As a result of this research, it has been determined that the same problems arise in the individuals staying home and recreational activity with family members are an important solution tool for overcoming these problems.…”
Section: Discussionmentioning
confidence: 99%
“…For involuntarily childless people the absence of children can have a multi-layered impact. Although research concerning childless people has been expanded, the prime focus has been on women (Hadley, 2021).…”
Section: Childlessness In Midlifementioning
confidence: 99%
“…They found a substantial group of never-partnered men living alone. Besides Jamieson ( 2009), Hadley ( 2019) is one of the few UK researchers that has considered the importance of family interactions on the health and social connectedness of older people by highlighting the case for looking particularly at men who are ageing without children and has made a strong case for childless older men being at increased risk of social isolation, loneliness, depression, ill health and increased mortality (see also Dykstra and Keizer 2009). Some research has demonstrated a link between the ageing without children and poor healthespecially formerly married childless men (Kendig et al 2007) in which the highest incidence of excessive smoking and drinking, worse physical health, depression, and sleeping difficulties have been recorded (Kendig et al 2007).…”
Section: Ageing Without Children In Relation To Gendermentioning
confidence: 99%